Preparation method of electromagnetic wave absorbent and electromagnetic wave absorbent
The method of combining PMMA microspheres with MXene nanosheets and Co-MOFs, followed by carbonization, addresses the poor absorption performance of MXene-based materials by creating a hollow heterostructure that increases interaction time and reduces impedance mismatch, resulting in enhanced electromagnetic wave absorption efficiency.
Patent Information
- Application Number
- CN202411859221.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Existing electromagnetic wave (EMW) absorption materials, such as MXene, suffer from poor absorption performance due to severe impedance mismatch, leading to secondary radiation and reduced effectiveness in EMW shielding.
A method involving the preparation of a composite electromagnetic wave absorber by mixing poly(methyl methacrylate) (PMMA) microspheres with MXene nanosheets, followed by the incorporation of cobalt metal-organic frameworks (Co-MOFs) through a combination of static self-assembly and in-situ growth, and subsequent carbonization to form a material with a hollow heterostructure, which enhances absorption by increasing interaction time and reducing impedance mismatch.
The resulting composite material exhibits improved electromagnetic wave absorption performance by prolonging wave propagation paths, increasing energy dissipation through multiple reflections and scattering, and providing a stable framework to prevent structural deformation, thereby enhancing the absorption efficiency and reducing frequency-dependent variations.
Smart Images

Figure CN119674561A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electromagnetic wave technology, and in particular to a preparation method of an electromagnetic wave absorber and the electromagnetic wave absorber. Background Art
[0002] With the advancement of electronic technology, more and more electronic technology products have entered human life. While enjoying the development of science and technology, humans are also facing the electromagnetic pollution caused by electronic technology products. High-efficiency electromagnetic wave (EMW) absorbing materials are considered to be functional materials with better ability to weaken the effect of electromagnetic waves. Electromagnetic wave absorbing materials can convert electromagnetic waves into Joule heat through dielectric loss and magnetic loss, and cause interference to cancel each other out, thereby suppressing or eliminating electromagnetic radiation.
[0003] The widespread use of electromagnetic waves has greatly promoted the development of human science and technology, but it has also brought some adverse effects to humans. For example, electromagnetic radiation may affect the normal operation of precision electronic instruments, cause information leakage, and may also threaten the life and health of living organisms.
[0004] Absorbing materials are materials that can absorb and attenuate incident electromagnetic waves, and dissipate them by converting them into heat or other forms of energy, thereby reducing the reflection and scattering of electromagnetic waves. They have great application value and demand in military and civilian fields. For example, MXene, a two-dimensional material with a large specific surface area and excellent conductivity, has received extensive attention and application in the field of electromagnetic interference shielding. However, as a shielding material, MXene will cause severe impedance mismatch, resulting in secondary radiation of electromagnetic waves, making the absorbing material's absorbing performance poor. Summary of the invention
[0005] The embodiment of the present application provides a method for preparing an electromagnetic wave absorber, aiming to improve the problem of poor wave absorbing performance of absorbing materials.
[0006] In the first aspect, the embodiment of the present application provides a method for preparing an electromagnetic wave absorber, comprising mixing a polymethyl methacrylate dispersion with a MXene colloidal solution and stirring to obtain a first precipitate, and drying the first precipitate to obtain a first mixed powder. The first mixed powder is dispersed in a first solvent to obtain a first dispersion. Cobalt salt is dispersed in a second solvent to obtain a second dispersion. And the MOFs organic ligand is dispersed in a third solvent to obtain a third dispersion. After the first dispersion and the second dispersion are mixed, they are mixed and stirred with the third dispersion to obtain a second precipitate, and the second precipitate is dried to obtain a composite material. The composite material is carbonized to obtain an electromagnetic wave absorber.
[0007] In some embodiments, the preparation of the polymethyl methacrylate dispersion includes: providing polymethyl methacrylate microspheres, dispersing the polymethyl methacrylate microspheres in a fourth solvent, and obtaining the polymethyl methacrylate dispersion. The particle size of the polymethyl methacrylate microspheres is 10 μm to 20 μm. The fourth solvent includes at least one of toluene, xylene, chloroform, tetrahydrofuran, and ethyl acetate.
[0008] In some embodiments, the polymethyl methacrylate dispersion and the MXene colloid solution are mixed and stirred to obtain a first precipitate, comprising mixing 50 ml to 150 ml of the polymethyl methacrylate dispersion with a concentration of 10 mg / mL to 15 mg / mL and 30 ml to 50 ml of the MXene colloid solution with a concentration of 2 mg / mL to 5 mg / mL, and stirring for 20 min to 40 min to obtain the first precipitate.
[0009] In some embodiments, the concentration of the first dispersion is 2 mg / mL to 5 mg / mL, the concentration of the second dispersion is 12 mg / mL to 15 mg / mL, and the concentration of the third dispersion is 7 mg / mL to 10 mg / mL.
[0010] In some embodiments, the carbonizing the composite material to obtain the electromagnetic wave absorber comprises placing the composite material at a temperature of 400° C. to 800° C. in an inert gas atmosphere for 2 to 4 hours at a heating rate of 1 to 2° C. / min to obtain the electromagnetic wave absorber. The inert gas comprises at least one of helium, argon, and nitrogen.
[0011] In some embodiments, the first solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol. The second solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol. The third solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol.
[0012] In some embodiments, the cobalt salt includes at least one of cobalt nitrate hexahydrate, cobalt chloride, cobalt sulfate heptahydrate, and cobalt carbonate.
[0013] In some embodiments, the MOFs organic ligand includes at least one of 2-methylimidazole, terephthalic acid, trimesic acid and 4-pyridinecarboxylic acid.
[0014] In some embodiments, the MXene comprises Ti3C2T x 、Ti2CT x 、V2CT x or Nb4C3T x At least one of .
[0015] In a second aspect, an embodiment of the present application further provides an electromagnetic wave absorber, which is prepared using the preparation method of the electromagnetic wave absorber as described in any one of the first aspects.
[0016] Different from the prior art, the embodiment of the present application provides a method for preparing an electromagnetic wave absorber. A polymethyl methacrylate dispersion is mixed with a MXene colloidal solution, and through an electrostatic self-assembly method, MXene nanosheets are adsorbed on polymethyl methacrylate microspheres, and cobalt ions are adsorbed on MXene nanosheets. Then, the cobalt ions and MOFs organic ligands are formed into Co-MOF through coordination bonds by an in-situ growth method, and a PMMA / MXene / Co-MOF composite material is obtained. The composite material is carbonized to form an electromagnetic wave absorber with a hollow heterogeneous structure. The electromagnetic wave absorber with a hollow structure can cause the incoming electromagnetic waves to be reflected and scattered multiple times in the cavity, prolong the propagation path of the electromagnetic waves in the electromagnetic wave absorber, and enhance the interaction time and opportunity between the electromagnetic waves and the electromagnetic wave absorber. The hollow structure can reduce the mutation of electromagnetic parameters and reduce impedance mismatch. Co-MOF itself has a specific crystal structure, and the cobalt ions and MOFs organic ligands form a stable three-dimensional framework structure through coordination bonds, which can provide a stable support framework for the electromagnetic wave absorber and reduce the deformation or collapse of the electromagnetic wave absorber during use. The cobalt ions in Co-MOF themselves have certain magnetism. When electromagnetic waves enter the composite material, magnetic losses will occur under the action of cobalt ions, and the energy of the electromagnetic waves will be converted into other forms of energy dissipation such as heat, thereby enriching the loss form of the electromagnetic wave absorber and enhancing the wave absorbing performance of the electromagnetic wave absorber. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] One or more embodiments are exemplarily described by the figures in the corresponding drawings, and these exemplary descriptions are not intended to limit the embodiments. Elements with the same reference numerals in the drawings represent similar elements.
[0018] Figure 1 This is a flow chart of some methods for preparing electromagnetic wave absorbers provided in the embodiments of the present application. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0020] Reference to "embodiment" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0021] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0022] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0023] The technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0024] In the first aspect, the present invention provides a method for preparing an electromagnetic wave absorber. Figure 1 , Figure 1 1 is a flow chart of a method for preparing some electromagnetic wave absorbers provided in the embodiments of the present application. The preparation method comprises the following steps:
[0025] Step S1: a polymethyl methacrylate dispersion and a MXene colloidal solution are mixed and stirred to obtain a first precipitate, and the first precipitate is dried to obtain a first mixed powder.
[0026] Polymethyl methacrylate (PMMA) is a high molecular polymer, also known as acrylic or organic glass. It has the advantages of high transparency, low price, and easy mechanical processing. It is a commonly used glass substitute material and is widely used in the preparation of transparent materials, medical equipment, building materials, and handicrafts. It is formed by the polymerization reaction of methyl methacrylate (MMA) monomer.
[0027] In some embodiments, the preparation of polymethyl methacrylate dispersion includes: providing polymethyl methacrylate microspheres, dispersing the polymethyl methacrylate microspheres in a fourth solvent, and obtaining a polymethyl methacrylate dispersion. Polymethyl methacrylate microspheres refer to polymethyl methacrylate particles with a particle size at the micron level. From the microscopic structure, the molecular chain of polymethyl methacrylate microspheres is mainly composed of carbon atoms to form the main chain, and the side chains contain ester groups and methyl groups. However, due to the microsphere form, it has a larger specific surface area. Among them, the particle size of the polymethyl methacrylate microspheres is 10μm to 20μm. The fourth solvent includes at least one of toluene, xylene, chloroform, tetrahydrofuran and ethyl acetate.
[0028] In some embodiments, in order to improve the dispersibility and stability of polymethyl methacrylate microspheres in the fourth solvent, a dispersant may be added. For example, the dispersant that can be added includes sodium dodecyl sulfate (SDS), polyethylene glycol (PEG), etc. The dispersant can be adsorbed on the surface of the microspheres, reduce the surface energy between the microspheres, and reduce the agglomeration between the methyl methacrylate microspheres. For example, the hydrophobic groups in the SDS molecules can interact with the surface of the methyl methacrylate microspheres, and the hydrophilic groups extend to the solvent, forming a stable steric hindrance effect, so that the microspheres can be evenly dispersed in the solvent.
[0029] MXene is a new type of transition metal carbide or carbonitride with a two-dimensional nanosheet structure. It is generally prepared by selectively removing the A atomic layer in the MAX phase through chemical etching and other methods. The general chemical formula of MXene can be expressed as M n+1 X n T x (Where M is an early transition metal element, X represents carbon or nitrogen, and T is the active group attached to the surface, such as -OH, -F, -O, etc.) Compared with graphene-based materials, MXene not only has the characteristics of high specific surface area, high conductivity, and good mechanical properties, but also its interlayer spacing and composition are adjustable and controllable. The rich surface functional groups such as -OH and -O give MXene better reactivity and hydrophilicity, allowing it to be well dispersed in aqueous solution. For example, MXene can be Ti3C2T x 、Ti2CT x 、V2CT x or Nb4C3T x MXene can effectively interact with electromagnetic waves and convert electromagnetic energy into heat energy or other forms of energy, thereby absorbing and scattering electromagnetic waves.
[0030] The preparation of MXene colloidal solution includes: mixing MXene with a polar solvent, such as deionized water. The functional groups on the surface of MXene, such as -OH, will form hydrogen bonds with water molecules, so that the MXene sheets can be dispersed in water to form a colloidal solution.
[0031] Polymethyl methacrylate dispersion and MXene colloidal solution can be prepared by electrostatic self-assembly to form PMMA / MXene composites.
[0032] Electrostatic self-assembly is a material preparation method based on electrostatic interaction. It is a process in which oppositely charged substances spontaneously assemble in a solution through electrostatic attraction to form a multilayer structure or composite material. In this process, no additional complex chemical reactions or physical means are required to force the substances to combine, but the natural attraction between charges is relied upon to enable the materials to be orderly arranged and combined at the molecular or nanoscale.
[0033] In the embodiments of the present application, the surface of the MXene material usually contains abundant polar functional groups (such as -H, =O and -F, etc.), which will be ionized in the aqueous solution, so that the MXene colloidal solution has a certain charge. The surface of the PMMA microspheres in the polymethyl methacrylate dispersion may also be charged, which may be due to the ionization of certain groups on the PMMA molecular chain under specific conditions. When the polymethyl methacrylate dispersion is mixed with the MXene colloidal solution, due to the effect of electrostatic attraction, the PMMA microspheres with opposite charges and the MXene colloidal particles will attract each other, so that the MXene nanosheets are adsorbed on the PMMA microspheres, thereby self-assembling to form a PMMA / MXene complex. The PMMA / MXene complex combines the advantages of both PMMA and MXene. Therefore, the prepared PMMA / MXene complex has the characteristics of high electrical conductivity, high thermal conductivity, good mechanical strength and toughness.
[0034] In some embodiments, a polymethyl methacrylate dispersion is mixed with a MXene colloid solution and then stirred to obtain a first precipitate, comprising mixing 50 ml to 150 ml of a polymethyl methacrylate dispersion having a concentration of 10 mg / mL to 15 mg / mL with 30 ml to 50 ml of a MXene colloid solution having a concentration of 2 mg / mL to 5 mg / mL, and stirring for 20 min to 40 min to obtain a first precipitate.
[0035] In some embodiments, the first precipitate is dried to obtain the first mixed powder, which specifically includes using a vacuum drying method to dry the first precipitate at a temperature of 60° C. to 80° C. for 8 h to 12 h.
[0036] Step S2: The first mixed powder is dispersed in a first solvent to obtain a first dispersion liquid. The first solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol. The concentration of the first dispersion liquid is 2 mg / mL to 5 mg / mL.
[0037] Step S3: The cobalt salt is dispersed in the second solvent to obtain a second dispersion. The cobalt salt includes at least one of cobalt nitrate hexahydrate, cobalt chloride, cobalt sulfate heptahydrate and cobalt carbonate. The second solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol. The concentration of the second dispersion is 12 mg / mL to 15 mg / mL. The MOFs organic ligand is dispersed in a third solvent to obtain a third dispersion. The MOFs (Metal-Organic Frameworks) organic ligand includes at least one of 2-methylimidazole, terephthalic acid, trimesic acid and 4-pyridinecarboxylic acid. The third solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol. The concentration of the third dispersion is 7 mg / mL to 10 mg / mL.
[0038] Step S4: After the first dispersion liquid and the second dispersion liquid are mixed, they are mixed and stirred with the third dispersion liquid to obtain a second precipitate, and the second precipitate is dried to obtain a composite material.
[0039] In-situ growth is a material synthesis technology, which refers to the use of chemical reactions or physical processes on the surface of a specific matrix material (or substrate) to make new materials grow directly from the surface of the matrix material to form a tightly integrated composite material system. In the above process, the matrix material provides a growth site, template or active center for the reaction for the newly grown material. There is a strong interaction between the newly grown material and the matrix material, such as chemical bonding, physical adsorption, etc., which enables them to form a whole.
[0040] The first dispersion and the second dispersion are mixed. The surface of the PMMA / MXene complex carries a negative charge because MXene itself carries a negative charge. The cobalt salt in the second dispersion contains cobalt ions after ionization. Through the electrostatic self-assembly method, the MXene with opposite charges and the cobalt ions attract each other, and the cobalt ions in the second dispersion can be adsorbed on the negatively charged MXene nanosheets through electrostatic adsorption. Then it is mixed with the third mixed solution. Through the in-situ growth method, the MOFs organic ligands coordinate with the cobalt ions, and the self-assembly and crystallization process are carried out in an orderly manner to form Co-MOF. Then, the second precipitate is obtained by centrifugation with deionized water or methanol, and the second precipitate is placed at a temperature of 60°C to 80°C and dried for 8h to 12h. A composite material is obtained, which is a PMMA / MXene / Co-MOF composite material.
[0041] Co-MOF itself has a specific crystal structure. Cobalt ions and MOFs organic ligands form a stable three-dimensional framework structure through coordination bonds, which can provide a stable support framework for the composite material and reduce the deformation or collapse of the composite material during use. The cobalt ions in Co-MOF themselves have certain magnetism. When electromagnetic waves enter the composite material, the electromagnetic waves will experience magnetic loss under the action of cobalt ions, and the energy of the electromagnetic waves will be converted into other forms of energy dissipation such as heat, thereby achieving the loss of electromagnetic waves.
[0042] Step S5: The composite material is carbonized to obtain an electromagnetic wave absorber.
[0043] Carbonization refers to the process of converting organic components into carbonaceous materials under specific conditions such as high temperature. PMMA microspheres are composed of carbon, hydrogen, and oxygen atoms, and are mainly concentrated inside the PMMA / MXene / Co-MOF composite material, mainly playing a supporting and structural adjustment role. Under high temperature conditions, the ester groups in the PMMA molecular chain begin to decompose, releasing gases such as carbon dioxide. These gases accumulate in the limited space inside the composite material, causing the material to expand locally and form a hollow structure electromagnetic wave absorber.
[0044] Electromagnetic wave absorbers with hollow structures can make incoming electromagnetic waves reflect and scatter multiple times in the cavity, prolong the propagation path of electromagnetic waves in the absorber, and enhance the interaction time and opportunity between electromagnetic waves and electromagnetic wave absorbers. During each reflection process, part of the energy of the electromagnetic wave will be absorbed or scattered, thereby reducing the energy of the electromagnetic wave that passes through the electromagnetic wave absorber. In addition, the hollow structure can make the electromagnetic wave absorber present a gradual distribution of electromagnetic parameters from the surface to the inside. The sudden change of electromagnetic parameters is reduced, thereby effectively reducing the impedance mismatch.
[0045] During the carbonization process, carbonaceous materials may interact with metallic components such as MXene and Co to form heterogeneous structures, and these heterogeneous structures will contain different phase interfaces, such as C-MXene interface and C-Co interface. When electromagnetic waves are transmitted to these interfaces, they will scatter in different directions, making the propagation path of electromagnetic waves inside the material complicated and prolonged, thereby enhancing the interaction time and opportunity between electromagnetic waves and electromagnetic wave absorbers.
[0046] In some embodiments, the composite material is carbonized to obtain an electromagnetic wave absorber, comprising placing the composite material at a temperature of 400°C to 800°C in an inert gas atmosphere, carbonizing for 2 hours to 4 hours, and heating at a rate of 1°C / min to 2°C / min to obtain the electromagnetic wave absorber. The inert gas includes at least one of helium, argon, and nitrogen.
[0047] The embodiment of the present application provides a method for preparing an electromagnetic wave absorber, wherein a polymethyl methacrylate dispersion is mixed with a MXene colloidal solution, and through an electrostatic self-assembly method, MXene nanosheets are adsorbed on polymethyl methacrylate microspheres, and cobalt ions are adsorbed on MXene nanosheets. Then, the cobalt ions and MOFs organic ligands are formed into Co-MOF through coordination bonds by an in-situ growth method, and a PMMA / MXene / Co-MOF composite material is obtained. The composite material is carbonized to form an electromagnetic wave absorber with a hollow heterogeneous structure. The electromagnetic wave absorber with a hollow structure can cause the incoming electromagnetic wave to be reflected and scattered multiple times in the cavity, prolong the propagation path of the electromagnetic wave in the electromagnetic wave absorber, and enhance the interaction time and opportunity between the electromagnetic wave and the electromagnetic wave absorber. The hollow structure can reduce the mutation of electromagnetic parameters and reduce impedance mismatch. Co-MOF itself has a specific crystal structure, and the cobalt ions and MOFs organic ligands form a stable three-dimensional framework structure through coordination bonds, which can provide a stable support framework for the electromagnetic wave absorber and reduce the deformation or collapse of the electromagnetic wave absorber during use. The cobalt ions in Co-MOF themselves have certain magnetism. When electromagnetic waves enter the composite material, magnetic losses will occur under the action of cobalt ions, and the energy of the electromagnetic waves will be converted into other forms of energy dissipation such as heat, thereby enriching the loss form of the electromagnetic wave absorber and enhancing the wave absorbing performance of the electromagnetic wave absorber.
[0048] In a second aspect, an embodiment of the present application further provides an electromagnetic wave absorber, which is prepared using the preparation method of the electromagnetic wave absorber according to any one of the first aspects.
[0049] The preparation method of the electromagnetic wave absorber is described below in conjunction with specific examples:
[0050] Example 1
[0051] (1) PMMA microspheres with a particle size of 10 μm were prepared into 100 mL of a dispersion with a concentration of 10 mg / mL, and 50 mL of a 2 mg / mL Ti3C2Tx colloidal solution was gradually added. The mixture was stirred for 30 min to obtain a first precipitate. The first precipitate was vacuum dried at 60 °C for 12 h to obtain PMMA / MXene powder, and the PMMA / MXene powder was stored under argon.
[0052] (2) Disperse 100 mg of PMMA / MXene powder in 50 mL of deionized water to obtain a first dispersion; dissolve 600 mg of Co(NO3)2·6H2O in 50 mL of deionized water to obtain a second dispersion; disperse 700 mg of 2-methylimidazole in 100 mL of deionized water to obtain a third dispersion. After mixing the first dispersion with the second dispersion, mix with the third dispersion, stir at room temperature for 24 h to obtain a second precipitate, and vacuum dry the second precipitate at 60 ° C for 12 h to obtain a PMMA / MXene / Co-MOF composite material.
[0053] (3) Under argon atmosphere, the PMMA / MXene / Co-MOF composite material was carbonized at a temperature of 600°C for 2 h at a heating rate of 1°C / min to obtain an electromagnetic wave absorber.
[0054] Example 2
[0055] (1) PMMA microspheres with a particle size of 10 μm were prepared into 100 mL of a dispersion with a concentration of 15 mg / mL, and 50 mL of a 5 mg / mL Ti3C2Tx colloidal solution was gradually added. The mixture was stirred for 30 min to obtain a first precipitate. The first precipitate was vacuum dried at 60 °C for 12 h to obtain PMMA / MXene powder, and the PMMA / MXene powder was stored under argon.
[0056] (2) Disperse 120 mg of PMMA / MXene powder in 50 mL of deionized water to obtain a first dispersion; dissolve 800 mg of Co(NO3)2·6H2O in 50 mL of deionized water to obtain a second dispersion; disperse 800 mg of 2-methylimidazole in 100 mL of deionized water to obtain a third dispersion. After mixing the first dispersion and the second dispersion, mix with the third dispersion, stir at room temperature for 24 h to obtain a second precipitate, and vacuum dry the second precipitate at 60 ° C for 12 h to obtain a PMMA / MXene / Co-MOF composite material.
[0057] (3) Under argon atmosphere, the PMMA / MXene / Co-MOF composite material was carbonized at a temperature of 800°C for 2 h at a heating rate of 2°C / min to obtain an electromagnetic wave absorber.
[0058] Comparative Example 1
[0059] (1) PMMA microspheres with a particle size of 10 μm were prepared into 100 mL of a dispersion with a concentration of 10 mg / mL, and 50 mL of a 2 mg / mL Ti3C2Tx colloidal solution was gradually added. The mixture was stirred for 30 min to obtain a first precipitate. The first precipitate was vacuum dried at 60 °C for 12 h to obtain PMMA / MXene powder, and the PMMA / MXene powder was stored under argon.
[0060] (2) Under an argon atmosphere, the PMMA / MXene powder was carbonized at a temperature of 600°C for 2 h at a heating rate of 1°C / min to obtain an electromagnetic wave absorber.
[0061] The electromagnetic wave absorbers prepared in Example 1, Example 2 and Comparative Example 1 were tested for wave absorption performance. The wave absorption performance results of different examples are shown in Table 1.
[0062] Table 1
[0063] Example Absorption loss(dB) Absorption bandwidth(GHz) Example 1 -50.14 7.36 Example 2 -48.59 6.56 Comparative Example 1 -21.35 2.55
[0064] According to the test results of the wave absorbing performance, by comparing the above embodiments and the comparative examples, the minimum reflection loss value RL when the thickness of the electromagnetic wave absorber in embodiment 1 is 2.25 mm is min The minimum reflection loss value RL when the thickness of the electromagnetic wave absorber in Example 2 is 1.82 mm is -50.14 dB, and the effective absorption band is 7.36 GHz. min The minimum reflection loss value RL when the thickness of the electromagnetic wave absorber in Comparative Example 1 is 3.05 mm is -48.59 dB, and the effective absorption band is 6.56 GHz. min It is -21.35dB, and the effective absorption band is 2.55GHz. It can be seen that the electromagnetic wave absorbers in Examples 1 and 2 have a strong ability to absorb electromagnetic waves, and the electromagnetic wave absorbers in Examples 1 and 2 can absorb a wider range of electromagnetic frequencies, effectively reducing the radiation effect of electromagnetic waves.
[0065] By comparing Example 1 and Comparative Example 1, the electromagnetic wave absorber in Comparative Example 1 has no Co-MOF structure, and has relatively fewer cavities and interfaces than the electromagnetic wave absorber in Example 1, and the reflection and scattering of electromagnetic waves in the electromagnetic wave absorber are relatively less. In addition, Example 1 has a Co-MOF structure, and the cobalt ions in the Co-MOF structure are magnetic and can cause magnetic loss of electromagnetic waves, thereby enriching the loss form of the electromagnetic wave absorber and enhancing the wave absorbing performance of the electromagnetic wave absorber. Therefore, the wave absorbing performance of the electromagnetic wave absorber in Comparative Example 1 is poorer than that of the absorber in Example 1.
[0066] The above disclosure is only the preferred embodiment of the present application, which certainly cannot be used to limit the scope of rights of the present application. Therefore, equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A method for preparing an electromagnetic wave absorber, characterized in that: include: The polymethyl methacrylate dispersion and the MXene colloidal solution are mixed and stirred to obtain a first precipitate, and the first precipitate is dried to obtain a first mixed powder; The first mixed powder is dispersed in a first solvent to obtain a first dispersion; The cobalt salt is dispersed in a second solvent to obtain a second dispersion; and the MOFs organic ligand is dispersed in a third solvent to obtain a third dispersion; After the first dispersion and the second dispersion are mixed, the mixture is mixed with the third dispersion to obtain a second precipitate, and the second precipitate is dried to obtain a composite material; The composite material is subjected to carbonization treatment to obtain an electromagnetic wave absorber.
2. The preparation method according to claim 1, characterized in that: The preparation of the polymethyl methacrylate dispersion comprises: Providing polymethyl methacrylate microspheres, wherein the polymethyl methacrylate microspheres are dispersed in a fourth solvent to obtain the polymethyl methacrylate dispersion; The particle size of the polymethyl methacrylate microspheres is 10 μm to 20 μm; The fourth solvent includes at least one of toluene, xylene, chloroform, tetrahydrofuran and ethyl acetate.
3. The preparation method according to claim 1, characterized in that: The polymethyl methacrylate dispersion and the MXene colloid solution are mixed and stirred to obtain a first precipitate, comprising: After mixing 50 ml to 150 ml of the polymethyl methacrylate dispersion with a concentration of 10 mg / mL to 15 mg / mL and 30 ml to 50 ml of the MXene colloid solution with a concentration of 2 mg / mL to 5 mg / mL, the mixture was stirred for 20 min to 40 min to obtain the first precipitate.
4. The preparation method according to claim 1, characterized in that: The concentration of the first dispersion is 2 mg / mL to 5 mg / mL; The concentration of the second dispersion is 12 mg / mL to 15 mg / mL; The concentration of the third dispersion liquid is 7 mg / mL to 10 mg / mL.
5. The preparation method according to claim 1, characterized in that: The step of carbonizing the composite material to obtain the electromagnetic wave absorber comprises: Under an inert gas atmosphere, placing the composite material at a temperature of 400° C. to 800° C., carbonizing for 2 h to 4 h, and heating at a rate of 1° C. / min to 2° C. / min, to obtain the electromagnetic wave absorber; The inert gas includes at least one of helium, argon and nitrogen.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The first solvent comprises at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol; The second solvent comprises at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol; The third solvent includes at least one of deionized water, methanol, ethanol, acetone, acetonitrile and propanol.
7. The preparation method according to any one of claims 1 to 5, characterized in that: The cobalt salt includes at least one of cobalt nitrate hexahydrate, cobalt chloride, cobalt sulfate heptahydrate and cobalt carbonate.
8. The preparation method according to any one of claims 1 to 5, characterized in that: The MOFs organic ligand includes at least one of 2-methylimidazole, terephthalic acid, trimesic acid and 4-pyridinecarboxylic acid.
9. The preparation method according to any one of claims 1 to 5, characterized in that: The MXene includes Ti3C2T x 、Ti2CT x 、V2CT x or Nb4C3T x At least one of .
10. An electromagnetic wave absorber, characterized in that: The electromagnetic wave absorber is prepared by the preparation method of the electromagnetic wave absorber according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite wave-absorbing material based on MXene and metal organic framework as well as preparation method and application of composite wave-absorbing material
CN112251193A
Multilevel heterostructure composite material, preparation method thereof and application thereof in electromagnetic microwave absorption
CN113174751A
MXene microsphere composite wave-absorbing material modified by spiny Ni elementary substance as well as preparation and application of MXene microsphere composite wave-absorbing material
CN114390880A
Wave-absorbing material with zero-dimensional / one-dimensional / two-dimensional composite nanostructure as well as preparation method and application of wave-absorbing material
CN114501966A
Magnetic MXene wave-absorbing composite material with corallite structure and preparation method
CN114655957A